2014
DOI: 10.3892/ijmm.2014.1637
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation patterns of steroid receptor genes ESR1, ESR2 and PGR in deep endometriosis compromising the rectum

Abstract: Endometriosis is characterized by the presence of endometrial-like tissue located outside the uterine cavity. Recent evidence suggests that endometriosis may be an epigenetic disease, as well as an estrogen-dependent disease. Based on the unique steroid hormone receptor expression profile observed in endometriotic lesions as compared to eutopic endometrium, the present study aimed to gain further insight into the DNA methylation patterns of alternative promoters of the steroid receptor genes ESR1, ESR2 and PGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…RASSF2 is widely expressed in humans and its down-regulation caused by aberrant promoter methylation had been found in a variety of primary malignant tumors and tumor cell lines [21,22], but it has not been reported to be related to ovarian cancer. A study on gastric cancer suggested that RASSF2 not only suppressed tumor growth directly but also inhibited inflammation and angiogenesis by inhibiting the Ras-signaling pathway [15]. This study supported that RASSF2 was a negative effector of the Ras signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…RASSF2 is widely expressed in humans and its down-regulation caused by aberrant promoter methylation had been found in a variety of primary malignant tumors and tumor cell lines [21,22], but it has not been reported to be related to ovarian cancer. A study on gastric cancer suggested that RASSF2 not only suppressed tumor growth directly but also inhibited inflammation and angiogenesis by inhibiting the Ras-signaling pathway [15]. This study supported that RASSF2 was a negative effector of the Ras signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
“…Study have demonstrated that epigenetic changes occur in both promoter regions B and A of the progesterone receptors (PGR) gene in intestinal EMS [15] and hypomethylation of estrogen receptor (ESR) β promoter might contribute to progesterone resistance in women with EMS [16]. ESR and PGR are quite always absent in the EAOC tissue [17], while we did not identify differentially methylated ESR and PGR genes by MCA-RDA in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Greatest differences were observed between the proliferative (peak E 2 ) and the midsecretory (peak P 4 ) phases, suggesting that epigenetic modifications play a role in normal endometrial steroid hormone responses, which can impact the tissue's functional and physiologic roles of pregnancy establishment and maintenance, tissue homeostasis after menses and regeneration, and endometrial disorders. With regard to endometriosis, aberrant promoter methylation of several genes whose products are critical for the normal endometrial P 4 response (e.g., PGRB , HOXA10 , ESR2 , SF1 ) has been reported in eutopic endometrium and ectopic disease in the pelvis of women with endometriosis and in animal models of the disease, with resulting resistance to P 4 action [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…Эпигенети-ческие изменения происходят в обоих промотерных регионах гена PGR при эндометриозе кишечника. Эутопический и эктопический эндометрий недоста-точно отвечают на действие прогестерона у женщин с эндометриозом [73].…”
Section: гормональные факторыunclassified